2004
DOI: 10.1097/01.shk.0000110622.42625.cb
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Initial Fluid Resuscitation on Subsequent Treatment in Uncontrolled Hemorrhagic Shock in Rats

Abstract: Using a modified uncontrolled hemorrhage shock model with massive splenic and vascular injury, we evaluated outcome and tissue oxidation injury with different resuscitation interventions during prehospital and hospital phases. The aim of our study was to explore the effect of initial fluid resuscitation on subsequent treatment of uncontrolled hemorrhagic shock in rats. Uncontrolled hemorrhagic shock was produced in 114 Wistar rat by sharp transection both of the splenic parenchyma at one location between the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…Relevant organ functions of the heart and kidneys showed a significant improvement according to the PiCCO measurement-treated group [27]. We attribute these results to better maintenance of systemic blood pressures leading to fewer requirements of catecholamines and improved perfusion of the kidneys which lowers systemic creatinin.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant organ functions of the heart and kidneys showed a significant improvement according to the PiCCO measurement-treated group [27]. We attribute these results to better maintenance of systemic blood pressures leading to fewer requirements of catecholamines and improved perfusion of the kidneys which lowers systemic creatinin.…”
Section: Discussionmentioning
confidence: 99%
“…Although a sufficient fluid resuscitation is necessary for anti-shock, recent studies have suggested that the massive fluid resuscitation before effectively controlling the active bleeding may increase the blood loss or lead to dilutional coagulopathy. In the meantime, the increase of blood pressure can peel away the scar tissue and lead a rebleeding, which may increase the probability of complications 18. In addition, intra-abdominal bleeding and increased death rate were reported for uncontrolled hemorrhagic shock animals that were perfused with the hypertonic saline 17.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, if intravascular volume expansion successfully restores cardiac output and arterial blood pressure before definitive hemostasis has been achieved, then, paradoxically, resuscitation can promote bleeding and shorten survival (4)(5)(6)(7)(8). Additionally, conventional approaches toward resuscitation require administration of large volumes of fluids that are intrinsically heavy and bulky.…”
Section: Introductionmentioning
confidence: 95%